Project Management Information System Audit with COBIT 5 Framework Focused on DSS Domains - Sumichan, Andrew; Gede Yudiyana, I Made; Sudarma, Made (International Journal of Engineering and Emerging Technology, 2019)
Information system management as a recording media for transactions, especially a construction project, is a management and financial strength for the company. Poor IT governance can cause various problems to arise and harm related parties that lead to company failures and losses. Auditing Information system is conducted to find the value of the maturity level of a management of information technology management in a company to fix existing problems. This study conducted an audit process on a project management information system with Cobit 5 Framework focusing on DSS domain. Study case is PT.K a contracting companies with the results of the capability level at the company is 2.16 and requires a quick fix on the DSS05 process.